Effect of nature-inspired needle-shaped vortex generators on the aerodynamic features of a double-delta wing. (15th July 2021) - Naeini, Hamed Khodabakhshian; Nili-Ahmadabadi, Mahdi; Park, Yoon Seong; Kim, Kyung Chun
Highlights: The effects of using new needle-shaped vortex generators in the apex and kink location of a double delta wing were experimentally studied by 2D planar PIV measurement. Flow visualizations were done at seven sections in the chord-wise direction and seven sections in the span-wise direction, and the plan-view of the wings was also targeted near the suction-side surface. The needle-shaped VGs have some notable positive effects on the vortical flow structure of the double-delta wing as cause the smaller vortices on the AKNS wing but more durable and stable structure due to its concentrated coherent vorticities comparing to the plain wing at high AOAs. The parameter Γ / Av was higher for the AKNS wing in a wide area of the double-delta wing surface, which represents the quantity of existing coherent vorticity distribution inside the vortex region over the wing. AKNS wing model has a narrower vortex structure with higher strength, more energetic flow near the wing surface with higher momentum, less reverse-flow regions and smaller wake which can enhance the lift, reduce the drag, and delay the stall. Abstract: The effects of using nature-inspired needle-shaped vortex generators (VGs) on the aerodynamic features of a 65°/35° double-delta wing were investigated experimentally in a wind tunnel. Particle Image Velocimetry (PIV) visualization was conducted on 7 chord-wise sections as well as 7 span-wise sections at an Angle of Attack (AOA) of 30° and on a plane adjacent to the wing surface at AOAs of 30° and 35° The experiments were carried out at Re  = 2 × 10 5 . The double-delta wing was equipped with a series of VGs at the leading edge of the apex and kink area. The effect of VGs on the time-averaged vortical flow features was investigated and then compared to those of the plain wing model. The assessment of the vortices' diameter, vorticity and velocity distribution, streamline topology, circulation (Γ), and parameter Γ/ Av showed that the use of the needle shaped VGs has an enhancing effect on the improvement in flow structure of the double-delta wing. The causes of the flow structure improvement were the increased flow momentum over and behind the wing, energized near-surface flow, a more concentrated vortex system, and delayed vortex breakdown. Graphical abstract: Image, graphical abstract